1968
DOI: 10.1111/j.1476-5381.1968.tb00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of a Gastric‐secretion Antagonist

Abstract: We embarked on the present study with the object of throwing light on the mode of action of gastrin. In this study a compound with specific antigastrin properties would seem to be useful. The actions of the pure natural peptides, gastrins I and II, in stimulating and inhibiting gastric acid secretion, as stimulants of pepsin and pancreatic secretion, and of gastric and small intestinal tone and motility, have been recorded by Tracy & Gregory (1964). Little is known of the mechanisms by which the gastrins displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1970
1970
1977
1977

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This effect of Metiamide could be due to increased gastrin secretion facilitated by the increase in pH of the gastric juice, as previously noted e.g. after 'antigastrin' (Kahlson, Rosengren & Svensson, 1968;Kobayashi & Maudsley, 1968;HAkanson & Liedberg, 1971). The discrepancy between the in vivo and in vitro determinations of histamine mobilization by pentagastrin in the presence of Metiamide is perhaps attributed to the reported activation of the histamine methyl transferase by small doses of the H2-receptor antagonist (Barth, Niemayer & Lorenz 1973).…”
Section: Discussionmentioning
confidence: 66%
“…This effect of Metiamide could be due to increased gastrin secretion facilitated by the increase in pH of the gastric juice, as previously noted e.g. after 'antigastrin' (Kahlson, Rosengren & Svensson, 1968;Kobayashi & Maudsley, 1968;HAkanson & Liedberg, 1971). The discrepancy between the in vivo and in vitro determinations of histamine mobilization by pentagastrin in the presence of Metiamide is perhaps attributed to the reported activation of the histamine methyl transferase by small doses of the H2-receptor antagonist (Barth, Niemayer & Lorenz 1973).…”
Section: Discussionmentioning
confidence: 66%
“…Its site of action is presumably the parietal cell proper. In a previous study from this laboratory it was demonstrated that the alleged 'Antigastrin' SC-15396, 2-phenyl-2-(2-pyridyl)-thioacetamide, acts by greatly reducing the sensitivity of the parietal and peptic cells to a variety of secretorily effective modes of stimulation (Kahlson, Rosengren & Svensson, 1968). At the present stage it appears reasonable to assume that atropine also, in a non-specific way, lowers the responsiveness of the parietal cell to stimulating influences.…”
Section: Discussionmentioning
confidence: 72%
“…Rats in which augmented interdigestive secretion occurred were excluded from further use. The absence of visual motor response in the pouch, and its presence in the main stomach under electrical stimulation of the vagus nerves in the neck, was also taken as evidence of effective vagal denervation (Kahlson, Rosengren & Svensson, 1968).…”
mentioning
confidence: 99%